Les pobres Griseldes s'anaren empobrint amb els segles. - BUTINYÀ, JÚLIA (Scripta, 2020)
Griselda's literary figure is a convincing example of a psychologically abused woman. Since the story of popular literature -source of the Decameron-, however, it has been changing its status. In order to observe the course in the following centuries, it is necessary to start from the medieval versions of Petrarch and Boccaccio, linked to that of Metge, as the story is spread through the Latin, Italian and Catalan versions. To deal with the thematic approach in Catalan texts, we resort to documentation of a popular or marginal nature, contrasting it with the course of Griseldian stories, including two famous Castilians. From the analysis we can see that the firmly humanistic defense of women by Metge, manifests in his Griselda, was interrupted everywhere, which will allow us to reflect on various issues of literary periodization.